Queer Performance and Contemporary Ireland - Walsh, Fintan. author. aut Link
IX, 189 p.
Keywords: This book examines the surge of queer performance produced across Ireland since the first stirrings of the Celtic Tiger in the mid-1990s, up to the passing of the Marriage Equality referendum in the Republic in 2015.